Enhancing the Social Problem Solving Skill by Implementing the Social Inquiry Learning Model in Primary School - Slamet Widodo; Achmad Anang Darmawan (Faculty of Teacher Training and Education, Universitas Terbuka, 2019)
The research was conducted on the basis of skills that must be mastered by students still limited to the low-level thinking. It was because the learning process conducted not to develop and to improve the skill of solving the problem. The purpose of this study was to describe the increase in the social problem-solving skills of students. The method of the research was class action research with instruments of the observation sheet, test and questionnaire sheet.There are 24 students of the 5th graders of elementary as the subjects of this research. The data analysis techniques were quantitative and qualitative descriptions. The conclusion of the research was that the social inquiry learning model could improve social problem-solving skills students. In the learning activity, the teacher was the facilitator by observing, guiding, and assessing the students’ activities in solving the problems. The activities of the students in solving the students were defining the problems, finding the alternative in solving the problems, choosing the most appropriate way, predicting the solution and evaluating. After the lesson was over, the students were happy and giving positive response because they were involved directly in solving the problems.